Sociology: An Introduction - Doob, Christopher Bates (Harcourt Press, 1997)
Keywords: Sociology; dept.soc; faculty_collection

Gauging the strength of evidence prior to plea bargaining: the interpretive procedures of court-appointed defense attorneys - Emmelman, Debra S (Law and Social Inquiry-journal of The American Bar Foundation, 1997)
An important debate among court observers is whether plea bargaining undermines the ideals of justice. This article presents findings that may reconcile some inconsistent research conclusions. It describes how, prior to plea bargaining, one group of court-appointed defense attorneys gauges the strength of evidence through a tacit, taken-for-granted process that emulates trial proceedings: based on their understanding of evidence in the legal community, defenders imagine a courtroom dialogue wherein the prosecution and defense take turns presenting their cases in front of a judge and jury. At issue throughout the dialogue is whether or to what extent information is sufficient, legal, and persuasive enough to convict the defendant. Because the process is part of the defenders' ongoing and unspoken daily routines, it may elude unsuspecting investigators. Ironically, this means not only that some analysts may inappropriately conclude that legal ideals play no role in plea bargaining but also that: others may ingenuously assume that such behavior is more ethical than it actually is.
Keywords: dept.soc